Medizinischer Fachwortschatz in deutschsprachigen Kinderwunschforen - Hanna Stypa (Linguistische Treffen in Wrocław)
This article focuses on the fertility forum, a type of online forum in which mainly women who need medical assistance to become pregnant can communicate with each other. The fertility forum has so far received little attention in linguistic research, although its specific nature makes it worthy of linguistic analyses from different perspectives. This article analyses the specialist medical vocabulary used by forum users in their posts. This aspect seems to be particularly interesting because the users are not experts in the field of infertility treatment options. The aim of the analysis was to excerpt the medical vocabulary, categorise it according to semantic criteria and determine the etymology, word formation and degree of specialisation of the terms. It has been possible to identify 94 examples of medical terms, which were classified into six groups: 1) terms relating to pregnancy in general, 2) terms relating to fertilisation, 3) terms relating to female physiology and anatomy, 4) terms relating to medical examinations, 5) terms relating to diseases, 6) terms relating to fertility treatments. Nearly half of the evidence is of foreign origin (Latin, Greek, English). With regard to the type of word formation, the following constructions were identified: composites, clippings or abbreviations, derivatives, multi-word terms, and simplices. With regard to the degree of specialisation, three levels could be distinguished.